TEXCT COMPLEXITY: THE LAST VICTIM OF THE WAR (STORY) BY OTKIR HOSHIMOV - Erkinova Muqaddas Olim qizi; Jo‘rayev Muhammadrahimxon Murod o‘g‘li (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  Text  complexity  constitutes  a  multidimensional  construct  that encapsulates  the  intricate  interplay  between  linguistic,  cognitive,  and  conceptual elements  within  written  discourse.  It  extends  beyond  mere  lexical  difficulty, encompassing syntactic sophistication, discourse cohesion, thematic profundity, and inferential demands placed upon the reader. Accurate assessment of text complexity necessitates  an  integrative  approach  combining  quantitative  metrics,  such  as readability  indices  and  corpus-based  analyses,  with  qualitative  evaluations  that consider narrative structure, genre-specific conventions, and conceptual abstraction. Moreover,  comprehension  is  profoundly  mediated  by  reader-intrinsic  factors, including prior knowledge, metacognitive strategies, and motivational orientation. A nuanced  understanding  of  text  complexity  is  pivotal  for  optimizing  pedagogical practices, facilitating  differentiated instruction,  and  promoting  higher-order  literacy skills,  thereby  fostering  critical  engagement  with  complex  texts  across  diverse educational contexts.